PENGARUH KINERJA KEUANGAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Firmanda, Alfifa Ayu; Wahyuni, Nanik (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The purpose of this study was to determine the effect of financial performance and environmental performance on firm value and managerial ownership as a moderator between financial performance and environmental performance on firm value. This study uses a quantitative approach with a purposive sampling technique. The results showed that the EVA value was 0.8075> 0.05, the MVA value was 0.5351> 0.05, the environmental performance value was 0.0151 <0.05, and the KM value between EVA and firm value was 0.7839> 0.05. The KM value between MVA and firm value is 0.0095 < 0.05, while the KM value between environmental performance is 0.6758 > 0.05. Thus, EVA and MVA do not affect firm value, while environmental performance has a significant effect on firm value, and managerial ownership as a moderating variable does not moderate the effect of EVA, and environmental performance on firm value. However, managerial ownership can moderate the relationship between MVA and firm value.